The Effectiveness of Role Playing Method in Learning Immune System Material on the Creativity and Learning Outcomes of High School Students - Nuridah, Armi; Partaya, Partaya (Journal of Biology Education, 2019)
The problem that occurs in the education world right now is the low learning outcomes and student creativity. Based on references, the roles playing method is an effective learning method for increasing student creativity and learning outcomes. The purpose of this study is to determine the effectiveness of the roles playing method on creativity and student learning outcomes and to find out the effectiveness of the roles playing method on learning the immune system. This research is a quasi-experimental research with nonequivalent control group design. The population are all students of grade 11 in MIA MAN 2 Semarang 2018/2019 school year. The sample is determined by purposive sampling and 2 classes have selected as the experimental class and the control class. In this study the experimental class carried out immune system learning using the roles playing method while the control class used the lecture method. The results showed that 85.56% of the experimental class students has creativity with creative to very creative categories while the control class is only 41.67% of students included in the creative and very creative categories. Student learning outcomes data show that the classical learning completeness of the experimental class is higher than the control class with a difference of 36.12%. The average value of learning outcomes and the average N-Gain score of the experimental class students also have a higher average value of the control class. The implementation of learning the roles playing method gained a score of 95.56%. Based on the description it can be concluded that the role playing method is effective on the creativity and learning outcomes of high school students and it can be concluded that the role playing method is effectively applied to learning the immune system because the results of the study already meet all the indicators that have been set.